2023
DOI: 10.1371/journal.pone.0289344
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of children’s physical activity profiles before and after COVID-19 lockdowns: A latent profile analysis

Ruth Salway,
Frank de Vocht,
Lydia Emm-Collison
et al.

Abstract: Physical activity is important for children’s health, but moderate to vigorous physical activity (MVPA) declines with age. COVID-19 lockdowns resulted in reduced MVPA and increased sedentary time among children. Characterising children’s activity patterns may help identify groups who are most likely to be inactive post-lockdown. Data were combined from a pre-COVID-19 cohort study on children aged 5–6 years (Year1: n = 1299), 8–9 years (Year4: n = 1223) and 10–11 years (Year6: n = 1296) and cross-sectional post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…61 Other recent evidence, including Active-6, has also found that the impact of the pandemic on child physical activity, and the recovery, is uneven across demographic groups such as gender, age, ethnicity and SES. 25,62 These findings are mirrored in this study, which suggest that children who were active before the pandemic lockdowns returned to active clubs, and those who were less active are now even harder to engage, resulting in a greater polarisation of child ability and activity levels. The Active-6 study has found that although child physical activity has returned to near pre-pandemic levels, 30 children are more dependent on organised activities, such as active clubs, for this physical activity.…”
Section: Discussionsupporting
confidence: 62%
“…61 Other recent evidence, including Active-6, has also found that the impact of the pandemic on child physical activity, and the recovery, is uneven across demographic groups such as gender, age, ethnicity and SES. 25,62 These findings are mirrored in this study, which suggest that children who were active before the pandemic lockdowns returned to active clubs, and those who were less active are now even harder to engage, resulting in a greater polarisation of child ability and activity levels. The Active-6 study has found that although child physical activity has returned to near pre-pandemic levels, 30 children are more dependent on organised activities, such as active clubs, for this physical activity.…”
Section: Discussionsupporting
confidence: 62%
“…We have recently proposed a new context-specific approach for school-based physical activity intervention design that emphasizes the varying needs of schools and the subsequent importance of a tailored approach ( 17 ). Between-school variability, attributable to unmeasured school factors, has shown to account for nearly double the amount of variation as individual factors ( 11 , 12 ). Yet, among the studies included in this review, few report descriptive information that can help to understand context, such as geographical location, socioeconomic characteristics, ethnicity, and school size.…”
Section: Discussionmentioning
confidence: 99%
“…Schools can provide an environment in which physical activity can be equitably promoted ( 9 , 10 ). Research shows that 13% of variability in weekday MVPA in primary school children on average can be attributable to school-level factors, almost double that of individual factors ( 11 , 12 ). Therefore, schools can provide an important role in promoting physical activity, especially during the pre-adolescent years (aged 7–11) where physical activity has shown to decline with age ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to patterns seen in children, where organised active clubs have become the mainstay of activity for children following lockdowns, 47 particularly active clubs based at the child's school, but this has been socio-demographically patterned. 46,47,62,63 The qualitative discussions highlighted the importance of social connection during the pandemic for increasing enjoyment and effort in physical activity. Connecting with others was often one of the main reasons for engaging in online physical activity and going for walks with friends.…”
Section: Discussionmentioning
confidence: 99%